Alexithymia and its association with burnout, depression and family support among Greek nursing staff - Giotakis Konstantinos; Moulou Aikaterini; Sikaras Christos; Tselebis Athanasios; Bratis Dionisios; Zoumakis Emmanuel; Ilias Ioannis (BMC, 2009)
Abstract Background Few studies have examined the relation between alexithymia (i.e. the inability to recognize and verbalize emotions) and professional burnout. Considering the absence of relevant studies in the Greek scientific literature, the aim of this work was to examine the associations of alexithymia with the three facets of professional burnout, the perception of family support and depression in nursing personnel. Methods The study was performed in one of the largest hospitals in Greece and included 95 nurses. Assessments of alexithymia, burnout, depression and family support were made by means of the Toronto Alexithymia Scale, the Maslach Burnout Inventory, the Beck Depression Inventory and the Julkunen Family Support Scale, respectively. Student's t-test, Pearson's correlation and stepwise linear regression were used for the evaluation of data. Results Alexithymia was correlated positively with depression, emotional exhaustion and depersonalization, and negatively with sense of family support and personal achievement. Additionally, family support was correlated positively with personal achievement and negatively with depression. Conclusion In the scientific literature there is a debate as to whether alexithymia is a stable personality characteristic or if it is dependent on symptoms of mental disorders. We tried to interpret the associations of alexithymia with professional burnout, depressive symptoms and family support. From this study it appears very likely that alexithymia is directly associated with depression and personal achievement, but also indirectly with the sense of family support.